Asymmetrical ring-shaped colloidal particles for self-assembly and superhydrophobic coatings. Issue 38 (21st April 2022) - Luo, Zhang; Li, Shanshan; Wang, Linna; Liu, Bing
Abstract : A frame-guided wetting strategy is reported to synthesize highly uniform but asymmetrical colloidal particles from rings to oblate ellipsoids through symmetrical discs for self-assembly of open 2D superstructures and superhydrophobic coatings. Abstract : A frame-guided wetting strategy is reported to synthesize highly uniform but asymmetrical colloidal particles from rings to oblate ellipsoids through symmetrical discs, which can self-assemble into diversified highly open 2D superstructures. In particular, ring-shaped particle monolayers have a higher contact angle of water than similar spherical ones, suggesting an attractive particle material for self-cleaning superhydrophobic coatings.